Real-world effects of once-daily inhaled steroid (fluticasone furoate) combined with long-acting beta-2 agonist (vilanterol) and long-acting muscarinic antagonist (umeclidinium) on lung function tests of asthma patients in Japan - Umeda, Akira; Shimada, Hisato; Yamane, Tateki; Mochizuki, Taichi; Inoue, Yasushi; Tsushima, Kenji; Miyagawa, Kazuya; Mochida, Atsumi; Takeda, Hiroshi; Okada, Yasumasa; Masaki, Katsunori; Matsusaka, Masako; et al. (Frontiers in Physiology, 2023)
Background: The Japanese drug use system allowed the once-daily use of inhaled corticosteroid fluticasone furoate (FF) combined with a long-acting beta-2 agonist vilanterol (VI) and a long-acting muscarinic antagonist umeclidinium (UMEC) against asthma on 18 February 2021. We investigated the real-world effects of these drugs (FF/UMEC/VI) mainly on lung function tests. Methods: This was an open-label, uncontrolled, within-group time-series (before-after) study. Prior asthma treatment (inhaled corticosteroid with/without a long-acting beta-2 agonist with/without a long-acting muscarinic antagonist) was switched to FF/UMEC/VI 200/62.5/25 μg. Subjects were evaluated by lung function tests prior to, and 1–2 months after, initiation of FF/UMEC/VI 200/62.5/25 μg. Patients were asked questions regarding the asthma control test and preference for drugs. Results: Overall, 114 asthma outpatients (97% Japanese) were enrolled from February 2021 to April 2022: 104 subjects completed the study. Forced expiratory volume in 1 s, peak flow, and asthma control test score of FF/UMEC/VI 200/62.5/25 μg-treated subjects were significantly increased (p<0.001, p<0.001, and p<0.01, respectively). In contrast with FF/VI 200/25 μg, instantaneous flow at 25% of the forced vital capacity and expiratory reserve volume were significantly increased by FF/UMEC/VI 200/62.5/25 μg (p<0.01, p<0.05, respectively). Sixty-six percent of subjects declared they wanted to continue FF/UMEC/VI 200/62.5/25 μg in the future. Adverse effects, mainly local, were seen in 30% of patients, but no serious adverse effects were seen. Conclusions: Once-daily FF/UMEC/VI 200/62.5/25 μg was effective against asthma without serious adverse events. This is the first report that demonstrated FF/UMEC/VI dilated peripheral airways using lung function tests. This evidence on drug effects may improve our understanding of pulmonary physiology and the pathophysiology of asthma.